2015
DOI: 10.1149/2.0521504jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Corrosion Resistance of AZ91 Alloy Produced by Semisolid Metal Processing

Abstract: Rheocast AZ91 magnesium alloy was evaluated in terms of microstructure and corrosion resistance. Rheocasting leads to a globular microstructure of α-Mg spheres separated by an interconnected β-Mg 17 Al 12 (β-phase) network. Findings revealed that early stages of corrosion were located at the center of α-Mg globules and more importantly at α-Mg/β-phase interfaces due to galvanic coupling as predicted from surface potential maps. Electrochemical, hydrogen evolution and weight loss measurements demonstrated the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…It has been shown that for a AZ91 alloy produced by rheocasting, the early stages of corrosion were located at the centre of α-Mg globules and more importantly at α-Mg/β-phase interfaces due to galvanic coupling. [41] Regarding galvanic coupling, corrosion around MnAl 2 inclusions is also reported to play a role in Mg-Al alloys. [60] Czerwinski et al [61] investigated the existence of chemical segregation within the primary grains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that for a AZ91 alloy produced by rheocasting, the early stages of corrosion were located at the centre of α-Mg globules and more importantly at α-Mg/β-phase interfaces due to galvanic coupling. [41] Regarding galvanic coupling, corrosion around MnAl 2 inclusions is also reported to play a role in Mg-Al alloys. [60] Czerwinski et al [61] investigated the existence of chemical segregation within the primary grains.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22,40 ] The corrosion resistance in a saline aqueous solution of a rheocast AZ91 alloy was ∼15 times higher in comparison with the same alloy produced via gravity cast. [ 41 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be noted that the α-Mg grain morphology in the studied RC AZ91D differs from the globular α-Mg morphology (with high aspect ratio) observed in the microstructure of a RC AZ91 material where the slurry was made by electromagnetic stirring. 38 EBSD mapping provided an opportunity to evaluate the low angle grain boundaries (LAGBs), boundaries with a misorientation < 15…”
Section: Resultsmentioning
confidence: 99%
“…However, there is limited knowledge on the microstructure and atmospheric corrosion behavior of the alloy RC AZ91D. Very recently, Mingo et al 38 studied the corrosion resistance of alloy AZ91 produced by RC process using electromagnetic stirring in 3.5 wt% NaCl at pH 6.5. They compared the corrosion results of the RC AZ91D with those of the alloy produced by gravity casting (GC) and reported a better corrosion resistance of RC AZ91D.…”
mentioning
confidence: 99%